2010
DOI: 10.1016/j.bbrc.2009.11.169
|View full text |Cite
|
Sign up to set email alerts
|

The effect of spermine on the initiation of mitochondrial protein synthesis

Abstract: Polyamines are important in both prokaryotic and eukaryotic translational systems. Spermine is a quaternary aliphatic amine that is cationic under physiological conditions. In this paper, we demonstrate that spermine stimulates fMet-tRNA binding to mammalian mitochondrial 55S ribosomes. The stimulatory effect of spermine is independent of the identity of the mRNA. The degree of stimulation of spermine is the same at all concentrations of mitochondrial initiation factor 2 (IF2 mt ) and mitochondrial initiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In a study, it has been found to act as a specific semen-derived sex pheromone in sea lamprey and promotes mating behaviors [ 161 ]. It is also evident to show antiinflammatory [ 162 ], mitochondrial protein synthesis [ 163 ], cardioprotective [ 164 ], and other effects. Lycopsamine exerted protective effects in spinal cord injury in rats by improving functional recovery and suppressing apoptosis [ 165 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study, it has been found to act as a specific semen-derived sex pheromone in sea lamprey and promotes mating behaviors [ 161 ]. It is also evident to show antiinflammatory [ 162 ], mitochondrial protein synthesis [ 163 ], cardioprotective [ 164 ], and other effects. Lycopsamine exerted protective effects in spinal cord injury in rats by improving functional recovery and suppressing apoptosis [ 165 ].…”
Section: Discussionmentioning
confidence: 99%
“…10). Spermine, for example, has been shown to regulate synthesis of mitochondrial proteins by stabilizing a small subunit of the ribosome and fMet-tRNA complex (71). Furthermore, recently Choo and Blenis (72) reported that rapamycin inhibited S6K in various cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the binding of polyamines to tRNA (36,37) enhances the association of the EF-Tu-GTP-aminoacyl-tRNA complexes with the ribosome. The Tabor lab reported that addition of polyamines to an auxotrophic strain of E. coli enhanced the production of a full-length protein dependent on a nonsense suppressor tRNA (38). Although the simple interpretation of this result is that polyamines are enhancing the utilization of the suppressor tRNA during elongation, additional experiments are needed to determine whether the polyamines are affecting the levels or aminoacylation of the suppressor tRNA.…”
Section: Polyamine Stimulation Of Translation In Vitromentioning
confidence: 99%